High moisture extrusion of soy protein concentrate: Influence of thermomechanical treatment on protein-protein interactions and rheological properties. (June 2019) - Pietsch, Valerie L.; Bühler, Jan M.; Karbstein, Heike P.; Emin, M. Azad
Abstract: This study aims at gaining a better understanding on the structuring mechanisms of soy protein concentrate (SPC) during high moisture extrusion. Formation of anisotropic structures was investigated at various process conditions, characterized by extruder temperature (100–143 °C), extruder pressure (1.7–2.7 MPa), and specific mechanical energy input (85–350 kJ/kg). At these conditions, anisotropy occurred with increased extrusion temperature. Compared to untreated SPC, no change in protein-protein interactions occurred for extruded samples. Applying a Closed Cavity Rheometer allowed investigating the influence of defined thermomechanical treatment on rheological properties. Increasing thermal treatment had a pronounced influence on flow behavior, causing a decrease in complex viscosity. Since protein-protein interactions were not influenced, these findings imply that structural changes of polysaccharides present in SPC could be responsible for the significant change in rheological properties, which is expected to play a major role on the formation of anisotropic structures. Highlights: Anisotropic structures occurred at T > 120 °C and SME >170 kJ/kg. Protein-protein interactions were not influenced during extrusion. Rheological properties were affected by thermomechanical treatment. Molecular changes of non-protein components influence rheological properties.